Uso de mindfulness no tratamento do zumbido: consenso baseado na opinião de especialistas brasileiros - Honorato, Mônica Claudino Medeiros (2025)
Tinnitus is a symptom that can be associated with various clinical conditions and is often considered difficult to manage. Among the available therapies, mindfulness has shown benefits such as reduced severity of the symptom, psychological suffering, and disability, as well as decreased distress caused by tinnitus. However, there is variability in the protocols regarding the number of sessions and the follow-up of these patients. The aim of this work is to develop a consensus among expert otolaryngologists, speech therapists, and physiotherapists regarding the recommendations and use of mindfulness applied to the treatment of tinnitus. This study will be observational, descriptive, quantitative, and cross-sectional. The research was conducted remotely and online through a websurvey hosted on the Google Forms digital platform. The sampling was convenience-based and included 23 specialists with recognized knowledge on the subject under study. We used the Delphi method, which consists of an artifice for structuring the communication of a group of experts on a complex subject by means of questionnaire interactions, divided into two stages. That are accompanied by feedback, keeping the participants' answers anonymous, in the search for a common result through statistical calculations. The first stage consisted of objective and subjective questions and we analysed them. The second stage consisted of 10 participants answering 34 questions derived from the themes and items that emerged from the answers in the first stage. The experts had to analyse each item and demonstrate their level of agreement on a five-point Likert scale. The content validity coefficient (CVC) was used to investigate the degree of agreement between the judges and select the final consensus items. Based on the results found, there was consensus on 25 of the 34 items (CVC ≥ 0.70). The experts consider that mindfulness is a therapeutic resource indicated for tinnitus, but not as the sole therapy for tinnitus (monotherapy). With regard to the frequency of application of this technique, there was consensus that it should be carried out once a week, with daily practice at home. There was also agreement that therapy can be followed up after 8 weeks using scales such as THI (Tinnitus Handicap Inventory) and VAS (Visual Analogue Scale). The only topic on which there was no consensus was the minimum number of sessions for remission. This study has the potential to improve the criteria for recommending and using mindfulness applied to the treatment of tinnitus. The findings may be useful for the development of future research and clinical recommendations in the area.